Effect of neurofeedback therapy based on virtual reality technology on anxiety in patients with anxiety disorder - Nassrin Rezaie Khosravi; Gelavij Mahmoodi (Shahid Beheshti University of Medical Sciences, 2018)
Background and purpose: Neurofeedback method and virtual reality technology are used as a relatively new therapy approach for the treatment of diseases and disorders. The aim of this study was to investigate the effect of neurofeedback therapy based on the virtual reality technology on anxiety in patients with anxiety disorder. Materials and methods: The present study was a semi experimental, pre-test, post-test and follow-up study with the control group. The statistical population of this study included adolescents with anxiety complaints to psychiatrists at the specialized clinic of Kermanshah health center in 2015 April and May. Method Available was used for sampling and the sample size included 5 people. Demographic and Beck Anxiety Inventories were used to collect the data. Participants were treated with neurofeedback based on virtual reality technology in three sessions. Data were analyzed using SPSS version 21 and Analysis of variance with repeated measurements. Results: The results showed that there was a significant difference between the mean anxiety scores in the pre-test phase and the post-test scores at the level of p <0.001. After two months, the results of follow-up were sustained. Conclusion: According to the results of this study, virtual reality technology based neurofeedback therapy reduces anxiety in people with anxiety disorder.